THE INFLUENCE OF LIQUIDITY, SOLVENCY AND FINANCING DISTRIBUTION ON THE PROFITABILITY OF ISLAMIC COMMERCIAL BANKS IN INDONESIA (PERIOD 2022-2024) - Abdushamad, Abdushamad; Fitria, Ana; Riza, Akmal (Faculty of Economics and Business, 2025)
One of the primary metrics used to evaluate the success of Indonesia's Islamic Commercial Banks (BUS) is profitability. The purpose of this study is to examine how the financing distribution (FDR), solvency (DER), and liquidity (CR) affected BUS's return on assets (ROA) during the period. Multiple linear regression was used to evaluate 39 observations of secondary data from 13 BUS. The findings show that ROA is positively and significantly impacted by CR and FDR, but not significantly by DER. These three factors together account for 62% of the variation in ROA. The findings emphasize the necessity of good liquidity management and funding distribution optimization in increasing the profitability of Islamic banks in Indonesia. This study's practical implications give management insights for boosting liquidity and financing methods in Islamic banking institutions, hence strengthening financial performance.